Activity on Trypanosoma cruzi, erythrocytes lysis and biologically relevant physicochemical properties of Pd(II) and Pt(II) complexes of thiosemicarbazones derived from 1-indanones - Santos, Diego (2012)
American trypanosomiasis or Chagas disease, caused by the protist parasite Trypanosoma cruzi (T. cruzi), is a major health concern in Latin America. In the search for new bioactive compounds, eight Pd(II) and Pt(II) complexes of thiosemicarbazones derived from 1-indanones (HL) were evaluated as potential anti-T. cruzi compounds. Their unspecific cytotoxicity was determined on human erythrocytes. Two physicochemical features, lipophilicity and redox behavior, that could be potentially relevant for the biological activity of these complexes, were determined. Crystal structure of [Pd(HL1)(L1)]Cl·CH3OH, where HL1 = 1-indanone thiosemicarbazone, was solved by X-ray diffraction methods. Five of the eight metal complexes showed activity against T. cruzi with IC50 values in the low micromolar range and showed significantly higher activity than the corresponding free ligands. Four of them resulted more active against the parasite than the reference antitrypanosomal drug Nifurtimox. Anti-T. cruzi activity and selectivity towards the parasite were both higher for the Pd(II) compounds than for the Pt(II) analogues, showing the effect of the metal center selection on the biological behavior. Among both physicochemical features tested for this series of compounds, lipophilicity and redox behavior, only the former seemed to show correlation with the antiproliferative effects observed. Metal coordination improved bioactivity but lead to an increase of mammalian cytotoxicity. Nevertheless, some of the metal complexes tested in this work still show suitable selectivity indexes and deserve further developments.